Humoral and cellular responses after COVID-19 vaccination in anti-CD20-treated lymphoma patients - Liebers, Nora; Speer, Claudius; Benning, Louise; Bruch, Peter-Martin; Krämer, Isabelle; Meißner, Julia; Schnitzler, Paul; Kräusslich, Hans-Georg; Dreger, Peter; Müller-Tidow, Carsten; Poschke, Isabel; Dietrich, Sascha (Blood, 2022)
TO THE EDITOR:Patients with hematological neoplasms, including lymphoma patients, have a high risk for severe COVID-19 diseases.1-4 COVID-19 vaccinations induce strong serologic and T-cell responses in immunocompetent humans and thereby effectively prevent severe COVID-19 disease courses.5-8 There is accumulating evidence that humoral immune responses after vaccination are impaired in patients with hematological malignancies, especially if they were treated with B-cell-depleting therapies such as anti-CD20 antibodies.9-11 However, there is limited information about the T-cell-mediated vaccine responses after anti-CD20 treatment. In this study, we investigated the humoral and cellular responses after COVID-19 vaccination in lymphoma patients who had received anti-CD20 treatment.